2022
DOI: 10.1038/s41591-022-01725-2
|View full text |Cite
|
Sign up to set email alerts
|

The MHC class I MICA gene is a histocompatibility antigen in kidney transplantation

Abstract: The identity of histocompatibility loci, besides human leukocyte antigen (HLA), remains elusive. The major histocompatibility complex (MHC) class I MICA gene is a candidate histocompatibility locus. Here, we investigate its role in a French multicenter cohort of 1,356 kidney transplants. MICA mismatches were associated with decreased graft survival (hazard ratio (HR), 2.12; 95% confidence interval (CI): 1.45–3.11; P < 0.001). Both before and after transplantation anti-MICA donor-specific antibodies (DSA) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…3 The hazard ratio for AMR among patients with both MICA and HLA preformed DSA was 25.68, P = 0.002. 3 The association between MICA antibody and allograft survival was confirmed in an independent validation cohort of 168 patients with biopsy-proven AMR. In the validation cohort, patients with anti-MICA DSA detected at the time of AMR were at higher risk for graft failure.…”
Section: Has the Time Come For Widespread Mhc Class I Mica Genotyping...mentioning
confidence: 90%
See 1 more Smart Citation
“…3 The hazard ratio for AMR among patients with both MICA and HLA preformed DSA was 25.68, P = 0.002. 3 The association between MICA antibody and allograft survival was confirmed in an independent validation cohort of 168 patients with biopsy-proven AMR. In the validation cohort, patients with anti-MICA DSA detected at the time of AMR were at higher risk for graft failure.…”
Section: Has the Time Come For Widespread Mhc Class I Mica Genotyping...mentioning
confidence: 90%
“…Donor-specific MICA antibodies identified either pretransplant or posttransplant were strongly associated with AMR (HR 3.79, P < 0.001), and the effect appeared to add to the risk of HLA DSA. 3 The hazard ratio for AMR among patients with both MICA and HLA preformed DSA was 25.68, P = 0.002. 3 The association between MICA antibody and allograft survival was confirmed in an independent validation cohort of 168 patients with biopsy-proven AMR.…”
mentioning
confidence: 90%
“…Among the first and most important studies to evaluate the role of anti-MICA antibodies in KT was that of Zou et al [ 59 ]. Subsequently, several studies have examined the importance of anti-MICA antibodies in KT and have shown that pre-transplant or post-transplant antibodies can be associated with the development of ABMR or TCMR and that they negatively impact kidney graft function [ 60 , 61 , 62 , 63 , 64 ]. The prevalence of anti-MICA antibodies in KT can be as high as 20% [ 65 ].…”
Section: Types Of Non-hla Ab In Kidney Transplantationmentioning
confidence: 99%
“…Additionally, anti-MICA antibodies could be found in the absence of sensitizing events that make the development of these antibodies through autoimmunity phenomena likely [ 66 ]. A mismatch between donor and recipient MICA alleles could lead to de novo anti-MICA donor-specific antibody formation, independent of HLA immunity [ 63 ]. These antibodies seem to exhibit synergistic action with anti-HLA antibodies, increasing the risk of rejection and graft loss [ 63 ].…”
Section: Types Of Non-hla Ab In Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation